Wykonaj działania i przeprowadź redukcję wyrazów podobnych:
a.8 +3(5-x²)(x²-5) -(x²-8)² +(4x²+2x-1)(x²-1)+2x
b.13-2(3-x²)(x²-3)+(x²+5)²-(3x²-3x-1)(x²-4)-3x³
c.(x+1)³-(2x-3)²-(x+3)²+2(x-2)(x+2)
d.(2x-5)²(x-1) -(3x+1)²(x+1) -(x-1)(x²+x+1)
e.(2x-1)³-(x+1)³+(x+2)³-(x+2)(x²-2x+4)
f.(2x-3y)²-(3x-y)(3x+y) +(x-2y)²-(8x-7y)(-2y)
g.(x²-1)³-(x-1)(x²+1)(x+1)+4x²(x²+1)
h.(3x-1)³-3(x+1)(x²-x+1)+2(x-2)³

1

Odpowiedzi

2009-11-25T18:25:39+01:00
A.8 +3(5-x²)(x²-5) -(x²-8)² +(4x²+2x-1)(x²-1)+2x=
8+3(5x²-25-x⁴+5x)-x⁴+64+4x⁴-4x²+2x³-2x-x²+1+2x=
8+15x²-75x⁴+15x-x⁴+64+4x⁴-4x²+2x³-2x-x²+2x=-71x⁴+2x³+10x²+15x+74
b.13-2(3-x²)(x²-3)+(x²+5)²-(3x²-3x-1)(x²-4)-3x³=
13-6x²+12+2x⁴+6x²+x⁴+25-3x⁴+12x²+3x³-12x+x²-4-3x³=13x²-12x+46
c.(x+1)³-(2x-3)²-(x+3)²+2(x-2)(x+2)=
x³+1-2x²+9-x²+9+2(x²+2x-2x-4)=x³+1-2x²+9-x²+9+2x²+4x-4x-8=
x³-x²+11
d.(2x-5)²(x-1) -(3x+1)²(x+1) -(x-1)(x²+x+1)=
(2x²+25)(x-1)-(3x²+1)(x+1)-(x³+x²+x-x²-x-1)=
2x³+25x-2x²-25-3x⁴-3x²+x+1-x³-x²-x+x²+x+1=-3x⁴+x³-5x²+25x-24
e.(2x-1)³-(x+1)³+(x+2)³-(x+2)(x²-2x+4)=
2x³-1-x³+1+x³+8-x³+2x²-4x-2x²+4x-8=x³
f.(2x-3y)²-(3x-y)(3x+y) +(x-2y)²-(8x-7y)(-2y)=
2x²+9y²-9x²-3xy+3xy+y²+x²-4y²+16xy+14y²=-6x²+20y²
g.(x²-1)³-(x-1)(x²+1)(x+1)+4x²(x²+1)=
x⁵-1-x³-(x³+x-1-x²-1)(x+1)+4x⁴+4x²=
x⁵-1-x³-x⁴-x²+x+x³+x-x³-x+1+x²+1+4x⁴+4x²=
x⁵+4x⁴-x³+4x²+x+1
h.(3x-1)³-3(x+1)(x²-x+1)+2(x-2)³=
3x³-1-3x³+3x²-3x-3x²+3x-3+2x³-16=2x³-20
1 1 1